Effects of sucrose reduction on the structural characteristics of sponge cake (Revista Ciência Agronômica, 2015)
The consumption of reduced-calorie cakes has been increasing, however this has presented challengesto be overcome concerning the formation of their structure when the sucrose is substituted by alternative sweeteners,gums or thickening agents. The present study evaluated the internal characteristics of cakes with a reduction in sucrose,and the effects of its substitution on starch gelatinisation. Starting with a pre-established formulation, the sucrose wasgradually substituted by a 1.0% mixture of sucralose in a 1.5% xanthan gum solution. In the substituted cake mix, theapparent viscosity and its thermal properties were evaluated using differential scanning calorimetry (DSC). Specificvolume (SV) and cell count (CC) were evaluated in the cakes. As the sucrose content decreased (52.17 to 10.00%), thespecific volume (1.94 to 0.7 mL/g), cell count (36.2 to 4.0 cell/cm²) and the apparent viscosity of the batter (337.56 to631.40 cP) were also reduced. The results showed that substituting the sucrose contributed greatly to the formation ofdefects in the cake structure (holes). From the data obtained, and thermograms of standard cake batters and those witha reduction in sucrose, it can be concluded that sucralose reduced the temperature of starch gelatinisation, speeding theprocess and causing compaction of the cake structure during baking, favouring the formation of bubbles throughout thebatter.